Implementation of multimedia elements in learning Malay language / Siti Radziah Azit - Azit, Siti Radziah (2005)
Language and communication are at the heart of the human experience. Malaysia must educate students who are linguistically equipped to communicate successfully in a pluralistic Malaysian society and abroad. This essential visualizes a future in which all students will develop and maintain proficiency in Malay Language. Foreign students who come to Malaysia from non-Malay backgrounds should also have opportunities to develop further proficiencies in Malay Language. This research is study on the implementation of multimedia elements in learning the Malay language. The prototype is designed based on user requirements, usability and the elements of multimedia. The usability is the effectiveness, efficiency and satisfaction where user can achieve a specified task in particular environment. As a result, it will identify the multimedia element in designing learning interface. The interviews are used to collect user requirements. In addition, usability testing and heuristic evaluation is used for evaluation of the interface. The interview and questionnaire is used in order to get the feedback from user and an expert. From the analysis, information is gained on the usability of the interface. The enhancement has done, based on the usability of the interface. Prototype is developed in order to give a clear view of the improvement interface.